2010
DOI: 10.1002/adem.201000120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functional Nanomaterials via Colloidal Mask Templating and Glancing Angle Deposition (GLAD)

Abstract: Currently there is strong focus on the fabrication of porous thin films with a nanoscale morphology, e.g., for the realization of new optical devices, [1][2][3][4][5][6] novel superior biocompatible materials, [7][8][9][10] 2-D surfaces for stem cell culture/ tissue engineering, [11,12] and high surface area supports for catalysts. [13] In particular porous low refractive index thin films have proven promising as antireflection coatings [5] and noble metal nanoparticles/nanostructured thin films (Pt, Au, Ag) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…For different in-vivo applications it is also critical that certain cells grow preferentially over others, a possibility that has been explored in-vitro by these same authors using OAD Pt films. In particular, they demonstrated that fibrinogen, an important blood protein, preferentially adheres to whisker-like nano-rough Pt substrates when compared to flat Pt surfaces, and that the proliferation of human fibroblasts is significantly reduced on these nanostructured surfaces [116]. Over the course of these studies, the growth of the film nanocolumns could be described by a power law relationship (see Sections 3.6 and 4.2) between the increments in their length and width [110].…”
Section: Cell-surface Interactionmentioning
confidence: 98%
See 2 more Smart Citations
“…For different in-vivo applications it is also critical that certain cells grow preferentially over others, a possibility that has been explored in-vitro by these same authors using OAD Pt films. In particular, they demonstrated that fibrinogen, an important blood protein, preferentially adheres to whisker-like nano-rough Pt substrates when compared to flat Pt surfaces, and that the proliferation of human fibroblasts is significantly reduced on these nanostructured surfaces [116]. Over the course of these studies, the growth of the film nanocolumns could be described by a power law relationship (see Sections 3.6 and 4.2) between the increments in their length and width [110].…”
Section: Cell-surface Interactionmentioning
confidence: 98%
“…For example, mass-produced metal wire grid polarizers are being fabricated via the OAD deposition of antireflection FeSi and SiO 2 layers on previously deposited aluminum columnar arrays [87,114,115]. Other emerging applications in biomedical areas [107,116,110,117], or for controlling the wetting properties of substrates [102,118], also rely on the use of patterned surfaces rather than the direct OAD of thin films (see Section 5.5).…”
Section: Oad On Nanostructured Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, the vacuum system should be able to handle high pressure sputtering conditions (larger than 10 −1 mbar) which might be required during sputter deposition. Different sputter geometries such as glancing angle deposition (GLAD) 25,26 and co-sputter experiments 27 should be feasible as well as heating and cooling of the sample substrate. Since the apparatus has been implemented in the P03 beamline to use GIXS methods, the sputter direction is downwards.…”
Section: A Design Requirementsmentioning
confidence: 99%
“…Here, we present a method by means of which we can synthesize unique platinum surfaces with controlled micro‐ and nano‐scale topographies through a combination of (GLAD) and colloidal surface patterning . Platinum was used since it offers a good biocompatibility and constitutes an integral part in various implantable electrodes.…”
mentioning
confidence: 99%